2021
DOI: 10.3389/fneur.2021.771803
|View full text |Cite
|
Sign up to set email alerts
|

Workflow Intervals and Outcomes of Endovascular Treatment for Acute Large-Vessel Occlusion During On-Vs. Off-hours in China: The ANGEL-ACT Registry

Abstract: Background: There may be a delay in or a poor outcome of endovascular treatment (EVT) among acute ischemic stroke (AIS) patients with large-vessel occlusion (LVO) during off-hours. By using a prospective, nationwide registry, we compared the workflow intervals and radiological/clinical outcomes between patients with acute LVO treated with EVT presenting during off- and on-hours.Methods: We analyzed prospectively collected Endovascular Treatment Key Technique and Emergency Work Flow Improvement of Acute Ischemi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…A Korean study investigated 8,957 AIS patients and reported that the weekend effect on ischemic stroke patients was associated with increased in-hospital and 30-day mortality rates, while the 7-day mortality rate showed no statistical significance, which was partially in accordance with our study ( 34 ). In China, Ding et al stated that off-hours admission was related to latency in the reperfusion time of EVT among AIS patients, but the delay was not associated with deteriorated functional appearance or higher mortality ( 35 ). However, their study included only some adult patients with acute large vessel occlusion who received EVT, which did not cover all AIS patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Korean study investigated 8,957 AIS patients and reported that the weekend effect on ischemic stroke patients was associated with increased in-hospital and 30-day mortality rates, while the 7-day mortality rate showed no statistical significance, which was partially in accordance with our study ( 34 ). In China, Ding et al stated that off-hours admission was related to latency in the reperfusion time of EVT among AIS patients, but the delay was not associated with deteriorated functional appearance or higher mortality ( 35 ). However, their study included only some adult patients with acute large vessel occlusion who received EVT, which did not cover all AIS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies on the off-hours admissions of patients with cerebrovascular and cardiovascular events have explained the weekend effect (35,(40)(41)(42)(43)(44). In a study involving 8 CSCs in the Specialized Programs of Translational Research in Acute Stroke (SPOTRIAS) cohort, the weekend effect was not observed (42).…”
Section: Discussionmentioning
confidence: 99%